(untitled) (Palimpsesto, 2017)
The novel "Carne de perra", represents an intimate and personal vision of the torture and vexations that occurred in Dictatorship, the duality of his voice allows to know the logics of operation of such period, through the tortures exercised by the omnipotent patriarchal figure and hegemonic of the Prince, Emilio Krank and the use and abuse that he makes of the identity of Maria Rosa, whose fractured subjectivity is rebuilding itself from the process of rememoration that realizes. When relating the novel with its sequel, my sister’s Scars story, it is evident, that the attempt to solve the trauma experienced is impossible, because it was destroyed physically, psychologically and emotionally by the ghosts of the past.